Victimization as a strategy of the artistic representation of the past: The case of the NATO bombing of the FRY - Mihaljinac Nina (Temida)
Using the research that mapped around 160 visual art works on the topic of NATO bombing of the FRY, the paper deals with the problem of incorporating various narratives of memory and artistic representations of collective traumas into the public memory discourse in Serbia (creation of sacrificial culture, rival memories, forgetting). The aim of the paper is to point out the possible methods of developing a holistic, inclusive and critical culture of remembrance that would lead to the treatment of collective traumas, and to underline the importance of showing public respect for all narratives of memory, and thus also narratives of victimization, which can often be politically abused. Therefore, the paper offers a new typology of representation of collective traumas, based on psychological analyses of types of traumatic reactions. The typology aims to achieve 1) equal appreciation of sufferings and all narratives of remembering, 2) critique of political misuses of narratives of trauma and reductionism. In order to overcome social tensions arising from the construction of the official sacrificial- patriotic narratives, it is necessary to break the binary constructed identities of “good” and “bad” ones, and to discover other narratives of the past, such as activist artistic memories.